The Relationship Between Curriculum, Learning Media, and Mental Health in Contemporary Islamic Education - Dede Indra Setiabudi; Cucu Zenab Subarkah; Laely Syaudah; Anjar Sulistyani; Buci Morisson; Meity Suryandari (Journal of Primary Education (JPE), 2026)
Mental health has become an increasingly important concern in higher education, particularly among prospective teachers who face academic, social, and technological challenges. Although previous studies have examined Islamic education, learning media, and student well-being separately, limited research has explored how curriculum and learning media jointly influence student mental health within Islamic higher education settings. This study aims to explore the relationship between curriculum implementation, learning media, and student mental health among PGMI students at Institut Agama Islam Al-Zaytun Indonesia. Using a qualitative case study approach, data were collected through observations, in-depth interviews, and document analysis involving PGMI students and lecturers. The findings reveal that an Islamic Education curriculum integrating spiritual values, character education, and humanistic learning contributes positively to students’ psychological well-being. Interactive digital learning media enhance engagement, learning motivation, and psychological comfort, while a religious academic environment strengthens emotional stability through social support and spiritual practices. However, excessive reliance on digital media may lead to digital fatigue and reduced social interaction. The novelty of this study lies in its integrated examination of curriculum, learning media, and mental health within contemporary Islamic higher education from students lived experiences. The findings suggest that Islamic higher education institutions should develop adaptive, humanistic, and spiritually oriented learning systems to promote student well-being and mental health.